Stress Indicators of Uda Rams Fed Graded Levels of Ensiled and Dried Cassava Peels in Semi-arid Region of Nigeria - Aljameel, K. M; Mika’ilu, M. M.; Musa, B. M. (European Journal of Applied Sciences, 2025)
The study was conducted at Kebbi State University of Science and Technology Aliero to access the effect of dried and ensiled cassava peels on stress indicators of Uda rams. A completely randomized experimental design (CRD) in a factorial layout (2 by 4) was used in this experiment with two processing methods (Dried and Ensiled) and graded levels (0, 10, 20 and 30) of formulated feeds representing treatments combinations, while each animal serves as replication. Rams fed ensiled cassava peels result shows treatment 3 have lower (P<0.05) rectal temperature readings compared to treatment 1 and 2. The result shows higher readings of pulse rate in treatment 2 compared to the other treatments. The result shows no significant variation (P<0.05) between the two forms of processing in all the parameters measured. The result shows interaction between level of inclusion and form of processing in terms of rectal temperature and respiratory rate. The study concludes that feeding ensiled or dried cassava peels does yield to any form as nutritional stress as indicated by the biomarkers (stress indicators) of the animals